2021
DOI: 10.3390/mti5020005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Steps and Game Elements in Gamified Fitness Tracker Apps: A Systematic Review

Abstract: This article reviews 103 gamified fitness tracker apps (Android and iOS) that incorporate step count data into gameplay. Games are labeled with a set of 13 game elements as well as meta-data from the app stores (e.g., avg rating, number of reviews). Network clustering and visualizations are used to identify the relationship between game elements that occur in the same games. A taxonomy of how steps are used as rewards is provided, along with example games. An existing taxonomy of how games use currency is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In other systematic reviews in the literature, the duties and responsibilities of the designers of gamification applications developed for use in the field of health, which gamification elements are preferred and similar issues have been investigated. In this study, the positive and negative effects of gamification applications on the use of fitness and the suggestions of other researchers on the subject were summarized [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other systematic reviews in the literature, the duties and responsibilities of the designers of gamification applications developed for use in the field of health, which gamification elements are preferred and similar issues have been investigated. In this study, the positive and negative effects of gamification applications on the use of fitness and the suggestions of other researchers on the subject were summarized [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wearable devices, such as smartphones and smartwatches, are able to monitor the health status and motivate individuals to conduct continuous excises. Studies have revealed that despite being aware of the health advantages of using fitness trackers to encourage themselves to stay active, many eventually stop using them [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was especially important since recent literature [15] suggests that positive effects reported for gamified interventions are considerably higher when compared to inactive control groups (such as individuals on waiting lists), rather than active control groups (where participants utilised a wearable device to track their physical activity or a non-gamified version of the app). In the domain of physical activity, goals are commonly integrated along with several other game elements that leverage social influences, such as competition and challenges [ [31] , [32] ]. Indeed, the three gamified conditions included in this protocol are social-oriented, include several game elements that are commonly adopted in industry practice [18] , and are designed on gamification design frameworks established in literature [ 2 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…There is an increasing number of fitness and health apps on the market, and as of the last quarter of 2021, there were estimated to be over 65,000 (Ceci 2022). There have been several reviews of existing mobile fitness apps (Tavares et al 2020;Neupane et al 2021). Tavares et al (2020) reviewed 36 related mobile apps from Google Play, updated between 2017 and 2020, none of which used a smartphone camera to capture the user.…”
Section: Related Workmentioning
confidence: 99%